Bio-organic fertilizers improve Dendrocalamus farinosus growth by remolding the soil microbiome and metabolome - Li, Shangmeng; Fan, Wei; Xu, Gang; Cao, Ying; Zhao, Xin; Hao, Suwei; Deng, Bin; Ren, Siyuan; Hu, Shanglian (Frontiers in Microbiology, 2023)
Organic and microbial fertilizers have potential advantages over inorganic fertilizers in improving soil fertility and crop yield without harmful side-effects. However, the effects of these bio-organic fertilizers on the soil microbiome and metabolome remain largely unknown, especially in the context of bamboo cultivation. In this study, we cultivated Dendrocalamus farinosus (D. farinosus) plants under five different fertilization conditions: organic fertilizer (OF), Bacillus amyloliquefaciens bio-fertilizer (Ba), Bacillus mucilaginosus Krassilnikov bio-fertilizer (BmK), organic fertilizer plus Bacillus amyloliquefaciens bio-fertilizer (OFBa), and organic fertilizer plus Bacillus mucilaginosus Krassilnikov bio-fertilizer (OFBmK). We conducted 16S rRNA sequencing and liquid chromatography/mass spectrometry (LC-MS) to evaluate the soil bacterial composition and soil metabolic activity in the different treatment groups. The results demonstrate that all the fertilization conditions altered the soil bacterial community composition. Moreover, the combination of organic and microbial fertilizers (i.e., in the OFBa and OFBmK groups) significantly affected the relative abundance of soil bacterial species; the largest number of dominant microbial communities were found in the OFBa group, which were strongly correlated with each other. Additionally, non-targeted metabolomics revealed that the levels of soil lipids and lipid-like molecules, and organic acids and their derivatives, were greatly altered under all treatment conditions. The levels of galactitol, guanine, and deoxycytidine were also markedly decreased in the OFBa and OFBmK groups. Moreover, we constructed a regulatory network to delineated the relationships between bamboo phenotype, soil enzymatic activity, soil differential metabolites, and dominant microbial. The network revealed that bio-organic fertilizers promoted bamboo growth by modifying the soil microbiome and metabolome. Accordingly, we concluded that the use of organic fertilizers, microbial fertilizers, or their combination regulated bacterial composition and soil metabolic processes. These findings provide new insights into how D.farinosus-bacterial interactions are affected by different fertilization regiments, which are directly applicable to the agricultural cultivation of bamboo.